Modelling and simulation of synchronization and engagement for self-energizing synchronizer with multibody dynamics. (March 2017) - Li, Jinning; Feng, Xingxing; Jiang, Ming; Zhang, Yunqing; Wan, Li
A multibody dynamic model of the self-energizing synchronizer in a 14-speed manual transmission gearbox is presented. While the contact forces between the engaged splines/teeth and friction torques between the synchro rings are hardly observed by conventional experiments, detailed contact and friction models in consideration of lubrication are established to simulate these contact/friction forces during shifting. The space motion of the sleeve is considered; thus, the differences in the contact forces between the engaged teeth can be simulated and observed. A pneumatic model is established to model the varying shift force acting on the synchronizer. An experiment is conducted for the self-energizing synchronizer to validate the presented synchronizer model. Moreover, to demonstrate the self-energizing function of the synchronizer, a synchronizer without self-energizing mechanism is modelled and compared with the original one.